Polysulfone/poly(ether sulfone) blended membranes for CO2 separation - Abdul Mannan, H. (John Wiley and Sons Inc., 2016)
Polymer blending as a modification technique is a useful approach for augmenting the gas-separation and permeation properties of polymeric membranes. Polysulfone (PSF)/poly(ether sulfone) (PES) blend membranes with different blend ratios were synthesized by conventional solution casting and solvent evaporation technique. The synthesized membranes were characterized for miscibility, morphology, thermal stability, and spectral properties by differential scanning calorimetry (DSC), field emission scanning electron microscopy, thermogravimetric analysis, and Fourier transform infrared (FTIR) spectroscopy, respectively. The permeation of pure CO2 and CH4 gases was recorded at a feed pressure of 2-10 bar. The polymer blends were miscible in all of the compositions, as shown by DSC analysis, and molecular interaction between the two polymers was observed by FTIR analysis. The thermal stability of the blend membranes was found to be an additive property and a function of the blend composition. The morphology of the blend membranes was dense and homogeneous with no phase separation. Gas-permeability studies revealed that the ideal selectivity was improved by 65 with the addition of the PES polymer in the PSF matrix. The synthesized PSF/PES blend membranes provided an optimized performance with a good combination of permeability, selectivity and thermal stability. Â© 2015 Wiley Periodicals, Inc.